Surface properties of aluminum alloy after laser processing and low-temperature heating; AIP Conference Proceedings; Vol. 2135 : Heat and mass transfer in the thermal control system of technical and technological energy equipment (HMTTSC 2019) - Batishcheva K. A. Kseniya Arturovna (2019, 2019)
Title screen